Validation of the Alcohol Use Disorders Identification Test (AUDIT) – Dusun Version in Alcohol Users in Sabahan Borneo - Nicholas Pang Tze Ping; Gloria Lee; Matthias Tseu; Jane Ivana Joss; Helda Artika Honey; Wendy Shoesmith; Sandi James; Jiann Lin Loo; Helen Lasimbang (2020)
Introduction: The Alcohol Use Disorder Identification Test (AUDIT) developed by WHO is instrumental in identifying individuals on the alcohol misuse spectrum. However there is no culturally appropriate Dusun language version in Sabahan Borneo. This study aims to develop and validate a Dusun language version of AUDIT (AUDIT-D). Methods: AUDIT was translated to Dusun and back translated to English and Malay. The first version was pilot tested in 20 participants and harmonised. The harmonised version was administered to 50 Dusun first language speakers fluent in Malay from villages in rural Sabah. Participants filled in socio-demographic questionnaires, Dusun (AUDIT-D) and Bahasa Malaysia (AUDIT-M) versions of AUDIT, and validated Bahasa Malaysia versions of the M.I.N.I. alcohol dependence subscale and CAGE. Results: ROC curves calculated AUDIT-D dependence cut-off of 9 and more, with prevalence of dependence at 46%. Factor analysis of AUDIT-D yielded a one - or three-factor solution, distinct from the AUDIT-M factor structure. Cronbach alpha coefficients for the total AUDIT-D was 0.83. Significant Spearman’s correlations existed between AUDIT-D and AUDIT-M scores (Spearman’s rho=0.999, p<.001). AUDIT-D and AUDIT-M were both significantlycorrelated with M.I.N.I. alcohol dependence subscales (rho=0.624 and 0.617 respectively, with p<0.0001).Both were not significantly correlated with CAGE. Conclusion: The AUDIT-D questionnaire has acceptable psychometric properties, properties and demonstrates similar factor structures to other areas with high alcoholdependence prevalence. It is suitable for the assessment and identification of alcohol use disorders in the unique Sabahan Borneo cultural landscape.